Characterization of wood‐laden flows in rivers. Issue 9 (1st May 2019) - Ruiz‐Villanueva, Virginia; Mazzorana, Bruno; Bladé, Ernest; Bürkli, Livia; Iribarren‐Anacona, Pablo; Mao, Luca; Nakamura, Futoshi; Ravazzolo, Diego; Rickenmann, Dieter; Sanz‐Ramos, Marcos; Stoffel, Markus; Wohl, Ellen
Abstract: Inorganic sediment is not the only solid‐fraction component of river flows; flows may also carry significant amounts of large organic material (i.e. large wood), but the characteristics of these wood‐laden flows (WLFs) are not well understood yet. With the aim to shed light on these relatively unexamined phenomena, we collected home videos showing natural flows with wood as the main solid component. Analyses of these videos as well as the watersheds and streams where the videos were recorded allowed us to define for the first time WLFs, describe the main characteristics of these flows and broaden the definition of wood transport regimes (adding a new regime called here hypercongested wood transport). According to our results, WLFs may occur repeatedly, in a large range of catchment sizes, generally in steep, highly confined single thread channels in mountain areas. WLFs are typically highly unsteady and the log motion is non‐uniform, as described for other inorganic sediment‐laden flows (e.g. debris flows). The conceptual integration of wood into our understanding of flow phenomena is illustrated by a novel classification defining the transition from clear water to hypercongested, wood and sediment‐laden flows, according to the composition of the mixture (sediment, wood, and water). We define the relevant metrics for the quantification and modelling of WLFs, including an exhaustive discussion of different modelling approaches (i.e. Voellmy, Bingham and Manning) and provide a first attempt to simulate WLFs. We draw attention to WLF phenomena to encourage further field, theoretical, and experimental investigations that may contribute to a better understanding of flows in river basins, leading to more accurate predictions, and better hazard mitigation and management strategies. © 2019 John Wiley & Sons, Ltd. Abstract : We collected evidences from 28 home movies from 7 countries to define and characterize wood‐laden flows. We propose a novel classification that encompasses a range from clear water to hypercongested wood debris flows, depending on the composition of sediment, wood and water. And we attempted to simulate this type of flows, discussing the application of different models.